Possible role of glial cells in the relationship between thyroid dysfunction and mental disorders - Noda, Mami (Frontiers in Cellular Neuroscience, 2015)
It is widely accepted that there is a close relationship between the endocrine system and the central nervous system (CNS). Among hormones closely related to the nervous system, thyroid hormones (THs) are critical for the development and function of the CNS; not only for neuronal cells but also for glial development and differentiation. Any impairment of TH supply to the developing CNS causes severe and irreversible changes in the overall architecture and function of human brain, leading to various neurological dysfunctions. In adult brain, impairment of THs, such as hypothyroidism and hyperthyroidism, can cause psychiatric disorders such as schizophrenia, bipolar disorder, anxiety and depression. Though hypothyroidism impairs synaptic transmission and plasticity, its effect on glial cells and cellular mechanisms are unknown. This mini-review article summarizes how THs are transported to the brain, metabolized in astrocytes and affect microglia and oligodendrocytes, showing an example of glioendocrine system. It may help to understand physiological and/or pathophysiological functions of THs in the CNS and how hypo- and hyper-thyroidism may cause mental disorders.